Beliefs, practices and periodontal treatment needs of an adult population in Cali, 2003. (Colombia Medica, 2006)
Objective: To identify the beliefs, practices and periodontal treatment needs in an adult population who assist to the clinics of the Colegio Odontológico Colombiano, Cali, 2003. Materials and methods: An observacional, descriptive cross sectional study was made. A proportional simple random sampling was used. A sample of 127 patients was obtained from the total number of attendants to the clinics of the Colegio Odontológico Colombiano. For data collection a questionnaire of 41 items (based on the health belief model) about the beliefs and practices of periodontal disease was used. Also, a clinical approach was made using the oral Greene & Vermilion hygiene index and the index of community periodontal index of treatment needs (CPITN). Results: Of the total, 69.3% believed that gum bleeding is a sign of disease; 65.4% believed that the cause of periodontal disease is the bad oral hygiene. 86.6% said that not having the disease helps to have a better social relation. 23% thought that preventing the periodontal disease is expensive. 2.3% had the oral hygiene index lower than the normal one of 12%, and 97.6% presented a sign of periodontal disease like bleeding, calculus, pockets. Conclusions: The Health Belief Model allowed to know the beliefs on periodontal disease. Although a great proportion of participants suffer periodontal disease, more than half of the population ignores that they suffer the disease. The participants do not have sufficient information about this disease. Although the participants feel susceptible and know the benefits of not having periodontal disease, almost all of them were affected.